Scar related border zone channels assessed with cardiac MRI are associated with ventricular arrhythmia in patients with ST-segment elevation myocardial infarction. (19th May 2022) - Thomsen, AF; Bertelsen, L; Jons, C; Jabbari, R; Lonborg, JT; Ekstrom, K; Tilsted, HH; Pedersen, F; Kober, L; Engstrom, T; Vejlstrup, N; Jacobsen, PK
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Prediction of scar-related ventricular arrhythmia in ST-Segment Elevation Myocardial Infarction (STEMI) is important, but currently difficult. Late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) permits characterization of left ventricular (LV) ischemic scars, including differentiation between core, border zone (BZ) and BZ channels. The latter represents potential electrical circuits of slow conductivity responsible for ventricular arrhythmic events. We hypothesized that detailed BZ channel characterization potentially serves as a risk marker for ventricular arrhythmia, therefore contributing to risk stratification following STEMI. Purpose: The aim of this study was to assess scar-related arrhythmic BZ channels with advanced CMR in STEMI patients developing subsequent ventricular arrhythmia compared with controls. Methods: This is a CMR sub-study of the DANAMI-3 STEMI multicenter trial (year 2011, n=1234) and Danegaptide phase II proof-of-concept clinical trial (year 2013, n=591). All patients were admitted for primary PCI in all primary PCI centers in Denmark. A total of 779 patients had a 3-month follow-up CMR. Of these, 21 patients subsequently experienced ventricular arrhythmia during 68 months of follow-up and were randomly matched 1:2 with 42 controls, who constituted the study population. Matching were based on left ventricular ejection fraction (LVEF), infarct location, culprit vessel, and revascularization status in patients with multivessel disease. Ischemic scar tissue including core, BZ and BZ channels were automatically detected by a specialized investigational software (1). To differentiate BZ from healthy tissue and BZ from core, thresholds of 40% ± 5% and 60% ± 5% of the maximum signal intensity were applied. A BZ channel in the LGE-CMR reconstruction was defined as a continuous corridor of BZ between 2 core areas or between a core area and a valve annulus (Figure 1). Results: We included 63 patients (median age: 58.0 years; 84% men; median LVEF: 45 ± 10%), of whom 30 (48%) patients had an anterior located infarction, and 45 (71%) patients were completely revascularized. The median time from STEMI to a ventricular arrhythmic event was 3 ± 2 years. A significantly higher number of patients with ventricular arrhythmia had BZ channels (n=16 (76%) vs. n=18 (43%), P=0.02) including an increased number of BZ channels (2 ± 2 vs. 1 ± 1, P=0.02) compared with controls. Patients with subsequent ventricular arrhythmia had a larger scar mass (core mass + BZ mass) (27 ± 17g vs. 19 ± 11g; P=0.03), core mass (9 ± 8g vs. 6 ± 5g; P=0.06) and BZ mass (18 ± 10g vs. 13 ± 7g; P=0.01). Conclusion(s): Border zone channels visualized by LGE-CMR were associated with subsequent development of ventricular arrhythmia in patients with STEMI and may serve as risk stratification following STEMI.